Magister Gratianus tanítása a házassági akadályokról - Herger, Cs. Eszter (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
Many legal scholars have examined the question of how to reconcile Gratian’s willingness to use both the Justinianic and the pre-Justinianic Roman law that he found in his sources with his apparent unwillingness or inability to use Justinian’s Roman law books at first hand. This paper focuses on another root of European legal culture, the Judaeo-Christian legal heritage. It addresses the question to what extent Gratian’s concept of marriage, based on a contemporary interpretation of the marriage of Mary and Joseph based on the decision of the Council of Ephesus (431), contributed to the clarification of the system of marriage impediments in 12th century canon law, and to what extent the magister used arguments based on biblical passages to do so. The canon law from the early Middle Ages allowed a husband to divorce his unfaithful wife, while the Western Church of Gratian’s age opposed the dissolution of the marriage bond and only recognised the possibility of separating the spouses from bed and table. Therefore, the significance of the subject lies primarily in the fact that in the case of some impediments to marriage the magister saw the possibility of dissolution of the unconsummated union (a so-called initiated marriage) and, in a few, not common cases of the consummated marriage too. The principle of indissolubility, although annulment and dissolution of marriage are different legal instruments, was not necessarily applied in this period either. However, Gratian’s particular concept of marriage and his legal explanations of the impediments to marriage contributed significantly to the fact that the only ground for divorce mentioned in the Gospels, adultery, could not lead to the dissolution of the bond. In the 16th century, Protestant divorce law was primarily a reaction to this understanding, and also the Catholic teaching on the impediments to marriage continued to evolve, formally still adhering to the principle of indissolubility.